PERHITUNGAN ASET TETAP PT.INALUM (PERSERO) BERDASARKAN SAK 16 DENGAN MENGGUNAKAN APPLICATION AND PROCESSING (SAP): PERHITUNGAN ASET TETAP PT.INALUM (PERSERO) BERDASARKAN SAK 16 DENGAN MENGGUNAKAN APPLICATION AND PROCESSING (SAP) - Ayu Kurnia Sari; Muhammad Hidayat (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Identify differences and gaps between existing practices and best standards to formulate recommendations for improvement. to find out the analysis of the success of its implementation and the factors needed by the company to optimize the success of SAP implementation. Identification of problems: indications of accounting recording errors in the calculation of PT INALUM's Fixed Assets using System Application And Processing (SAP). There were findings by an independent external auditor regarding the recording of PT INALUM's fixed assets. The research results stated that the calculation of PT INALUM's fixed assets. Inalum (Persero) based on SAK 16 using Application and Processing (SAP) has several advantages and challenges. Implementing SAP can increase efficiency, accuracy and transparency of fixed asset information. However, implementing SAP also requires quite high implementation, training and maintenance costs.